Leclercia adecarboxylata in Peritoneal Dialysis Patients: A Systematic Review - John Dotis; Antonia Kondou; Vasiliki Karava; Georgia Sotiriou; Athina Papadopoulou; Charalampos Zarras; Chrysi Michailidou; Eleni Vagdatli; Nikoleta Printza (MDPI AG, 2023)
Background: Leclercia adecarboxylata is a Gram-negative bacillus that can rarely cause infections in humans. We recently treated a case of peritonitis due to L. adecarboxylata in a peritoneal dialysis (PD) pediatric patient, and we systematically reviewed all the relevant reported cases in the literature. Methods: We searched the PubMed and Scopus databases, and we reviewed 13 such cases (2 children, 11 adults) that were reported, including our patient. Results: The mean (±SE) age was 53.2 ± 22.5 years, with a male-to-female ratio of approximately 1:1.6. Their mean vintage period on PD prior to L. adecarboxylata peritonitis was 37.5 ± 25.3 months. The VITEK card was the identification diagnostic tool in most cases (63%). The antimicrobial agent that was most frequently used was ceftazidime, which was implemented in 50% of cases as initial therapy, either as a monotherapy or combination therapy; in only two patients (15.3%) was the Tenkhoff catheter removed. The median duration of treatment was 18 days (range of 10-21 days), and all 13 patients that were reviewed were healed. Conclusions: Physicians should be aware that L. adecarboxylata is noted to rarely cause peritonitis in PD patients; however, this pathogen seems to be sensitive to most antimicrobial agents and can result in a favorable outcome with the selection of appropriate treatment.